DIFUSI INOVASI APLIKASI MY RSWN DALAM PELAYANAN KESEHATAN DI RSUD K.R.M.T WONGSONEGORO KOTA SEMARANG - Setiya Rini, Diyah; Santoso, R. Slamet (Journal of Public Policy and Management Review, 2025)
RSUD K.R.M.T Wongsonegoro, Semarang City, as a hospital owned by the Semarang City Government developed the My RSWN application innovation to facilitate online registration and access to other health services. However, there are several problems that indicate that the diffusion of My RSWN application innovation has not been optimal. This research aims to analyze the diffusion of innovation process and the factors inhibiting the diffusion of innovation the My RSWN application. This research applies a descriptive qualitative approach using interview, observation and documentation data collection techniques. The research results show that the diffusion of innovation the My RSWN application has generally gone well, but there are several aspects of innovation diffusion that have not been fulfilled. Innovation meets the attributes of relative advantage, suitability, testability and observability. The communication channels used are mass media and interpersonal. The time period in terms of when the application is created is sufficient and its acceptance through the stages of the innovation decision process. The hospital's social system has been supportive, as can be seen from the support of leaders, collaboration with Health Facility 1, and acceptance of innovation by employees as a group. The innovation diffusion element that has not been fulfilled is the innovation in the complexity attribute. The inhibiting factors are psychological barriers at the level of experience of people who are less familiar with technology, practical barriers to technical availability in terms of system errors and limitations in people's devices, and the age factor. The suggestions given are completing the FAQ menu, providing a guide to using the application in the information section, updating the application regularly and completing the online registration website with a menu like in the application, and providing a special information service counter for the elderly.